Análise epidemiológica e hematológica de ovinos (ovis aries) no semiárido paraibano - Ferreira, Rafael da Rocha (2023)
Sheep farming in the northeast region plays an important social and economic role in the family farming segment, with sheep farming having a prominent role in this segment. Knowledge and situational diagnosis are instruments that help and identify barriers in the productive sector, helping in decision-making and formation of public policies. The objective of this work was to characterize and typify the sheep farming system of small ranchers in the municipalities of: Baraúna, Nova Palmeira and Picuí, to know the hematological indices and the prevalence of Brucella abortus in sheep in the studied region. The work was carried out in the Borborema mesoregion, Microregion of the Eastern Seridó of Paraíba between the months of November 2022 and May 2023, targeting family farmers in the municipalities of Baraúna, Nova Palmeira and Picuí. 42 properties were worked and samples were collected from 611 animals, all sheep of both sexes aged over 2 months, excluding females in the final third of pregnancy. The primary quantitative information was obtained from socioeconomic and epidemiological questionnaires, while the blood samples were obtained through blood puncture of the jugular vein, stored in two divided tubes: with EDTA and without EDTA, packed in isothermal boxes with temperatures between 2 and 8 ºC duly labeled with the name of the property and the number of the animal, subsequently the hematological analysis was carried out using a model analyzer SCILVETABCPLUS to obtain the number of red blood cells, hematocrit, hemoglobin and total leukocytes, since the cell differentiation was made through blood smears stained with panotic fast. The determination of the prevalence of B. abortus was performed using the Acidified Buffered Antigen (AAT) test. We had as results: most family farmers own their own land (80,95%), having low schooling with high illiteracy rates (16,67%), income below the minimum wage (61,90%), having as a family group active in activities agricultural/livestock between 4 and 6 people (42,86%). The lack of training was also evident (61,90%). We can highlight the failure to carry out sustainable practices for living with the drought, such as forage conservation (83,33%), haymaking and silage, the vast majority being dependent on the purchase of roughage and concentrate in local markets (69,05%), thus contributing to most of the small cattle raisers have a semi-intensive breeding system (76,19%). With regard to hematological indices, we had a prevalence of 7,20% of anemic animals found in 33,33% of the properties, and leukocytosis and leukopenia 4,42% and 3,76% of the animals present in 28,57% and 19,05% of the properties, respectively. Finally, no positive animals for brucellosis were found in the 611 samples tested.